The Effect Of Financial Distress And Profitability On Auditor Change In Consumption Goods Sector Companies Listed On The Indonesia Stock Exchange In 2018-2021 - Sabarno Dwirianto; Roza Linda; Nanda Suryadi (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research is entitled influence, financial distress, and profitability of changing auditors in consumer goods sector companies listed on the Indonesia Stock Exchange in 2018-2021. The purpose of this study is to find out how financial distress and profitability of auditor changes. This study uses logistic regression by analyzing the factors that have occurred. This study uses secondary data with a population of 52 companies and a sample of 23 companies, namely companies in the consumer goods sector on the IDX. This research produces interesting findings, including financial distress which has a significant effect on auditor turnover. Meanwhile, the profitability variable has no effect on auditor turnover. The impact of the results of this study is the determination of the variables used by 37.5%, there are still 62.5% of other variables that can be used as further research such as corporate governance variables, operational complexity, ownership structure.